2023
DOI: 10.1017/jfm.2023.281
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental time scales of bubble fragmentation in homogeneous isotropic turbulence

Abstract: We investigate the fundamental time scales that characterise the statistics of fragmentation under homogeneous isotropic turbulence for air–water bubbly flows at moderate to large bubble Weber numbers, $We$ . We elucidate three time scales: $\tau _r$ , the characteristic age of bubbles when their subsequent statistics become stationary; $\tau _\ell$ , the expected lifetime of a bubble before further fragmentation; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…However, this hypothesis has been challenged recently (Vela-Martín & Avila 2021;Qi et al 2022), and it is found that sub-bubble-scale eddies may also contribute to the breakup process, resulting in a shorter time scale. In addition to the eddy time scale, more time scales relevant to the breakup process have been proposed (Ni 2024), including the bubble natural oscillation time scale (Lamb 1879;Risso & Fabre 1998), the capillary time scale (Villermaux 2020; Rivière et al 2022;Ruth et al 2022), the bubble lifetime (Martínez-Bazán, Montanes & Lasheras 1999;Liao & Lucas 2009;Qi, Masuk & Ni 2020;Vela-Martín & Avila 2022), the large-scale shear time scale (Zhong & Ni 2023), and the convergent time scale (Qi et al 2020;Gaylo, Hendrickson & Yue 2023). However, the relationship among those time scales remains unclear, particularly how this relationship is connected to the Weber number We = ρ 2/3 D 5/3 /σ , where ρ, , D and σ are the density, turbulence dissipation rate, bubble diameter and surface tension coefficient, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, this hypothesis has been challenged recently (Vela-Martín & Avila 2021;Qi et al 2022), and it is found that sub-bubble-scale eddies may also contribute to the breakup process, resulting in a shorter time scale. In addition to the eddy time scale, more time scales relevant to the breakup process have been proposed (Ni 2024), including the bubble natural oscillation time scale (Lamb 1879;Risso & Fabre 1998), the capillary time scale (Villermaux 2020; Rivière et al 2022;Ruth et al 2022), the bubble lifetime (Martínez-Bazán, Montanes & Lasheras 1999;Liao & Lucas 2009;Qi, Masuk & Ni 2020;Vela-Martín & Avila 2022), the large-scale shear time scale (Zhong & Ni 2023), and the convergent time scale (Qi et al 2020;Gaylo, Hendrickson & Yue 2023). However, the relationship among those time scales remains unclear, particularly how this relationship is connected to the Weber number We = ρ 2/3 D 5/3 /σ , where ρ, , D and σ are the density, turbulence dissipation rate, bubble diameter and surface tension coefficient, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of these exchanges is determined by the product of the interfacial flux and the interfacial area, emphasizing the pivotal role of interfacial characteristics. There has been considerable effort to estimate these exchanges via empirical correlations (Akita & Yoshida 1974;Kelly & Kazimi 1982;Delhaye & Bricard 1994) or via population balance equations relying on the droplet size distribution and on droplet breakage and coalescence models (Luo & Svendsen 1996;Babinsky & Sojka 2002;Andersson & Andersson 2006a,b;Martínez-Bazán et al 2010;Chan et al 2018;Chan, Johnson & Moin 2021;Gaylo, Hendrickson & Yue 2023). Hence, in this study we aim to answer the question, 'what is the interfacial area of surfactant-laden droplets in turbulence?'…”
Section: Introductionmentioning
confidence: 99%
“…It was shown also that, in the absence of coalescence, the breakage rate depends on the Weber number alone. Gaylo et al (2023) investigated the fragmentation of bubbles in statistically stationary homogeneous isotropic turbulence and characterized several fundamental time scales of the bubbles: the relaxation time, the expected lifetime and the time needed for the largest bubble to break down to the Kolmogorov-Hinze scale.…”
Section: Introductionmentioning
confidence: 99%